Menumbuhkan Jiwa Kewirausahaan dan Peran Profesi Akuntan di SMKN 9 Jakarta Barat - Kusumabrata, Indraguna (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: As a result of this community service project, students at SMK Negeri 9 West Jakarta are expected to acquire an entrepreneurial spirit and an awareness for the significance of the accounting profession. Students who graduate from SMK, especially accounting majors, will be better equipped to explore the wide range of career options in business and management. Methodology/approach: The project began with site identification and needs assessment, followed by field observation, material preparation, permits, promotion, training, and a final report. Offline activities included an accounting role presentation, sharing of entrepreneurial experiences, and a Q&A session. Results/findings: This activity fosters broader insight and motivation for students to prepare themselves in meeting and facing the needs of the workforce. In addition, it increases students' understanding of careers according to their interests and abilities and has career choices in the future. After graduating from school, students can make a curriculum vitae to apply for a job and ethics in professional work. Conclusions: This community service activity helps students develop knowledge and skills relevant to the workforce, while enhancing self-confidence, competencies aligned with their interests, and readiness to compete in an increasingly competitive job market. Limitations: This activity is limited to XII grade students, majoring in accounting at State Vocational High Schools (SMKN) 9 West Jakarta in 2024. Contribution: Grade XII students at SMKN 9 West Jakarta gain benefits through understanding the importance of accounting, developing an entrepreneurial mindset, and exploring career paths as employees, entrepreneurs, or pursuing higher education.